2003
DOI: 10.1074/jbc.m212183200
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Molecular Cloning of a Novel Keratan Sulfate Hydrolase, Endo-β-N-acetylglucosaminidase, from Bacillus circulans

Abstract: Keratan sulfate (KS) is degraded by various enzymes including endo-␤-galactosidase, keratanase, and keratanase II, which are used for the structural analysis of KS. We purified a novel KS hydrolase, endo-␤-N-acetylglucosaminidase, from the cell pellet and conditioned medium of Bacillus circulans, by sequential chromatography using DE52 and phenyl-Sepharose columns with ϳ63-and 180-fold purity and 58 and 12.5% recovery, respectively. Like keratanase II of Bacillus sp. Ks36, the enzyme, designated Bc keratanase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…More generally, we now have six families of GHs encompassing enzymes degrading sulfated polysaccharides: families GH16 (κ-carrageenases, keratanases), GH79 (heparanases), GH82 (ι-carrageenases), a new GH family specific for the degradation of sulfated fucans [46] and two unclassified enzymes, Bacillus circulans keratanase II [47] and P. carrageenovora λ-carrageenase (the present study). With the exception of the GH16 family, all these families encompass enzymes that interact exclusively with anionic polysaccharides.…”
Section: Insights Into the Evolution Of Carrageenase Familiesmentioning
confidence: 81%
“…More generally, we now have six families of GHs encompassing enzymes degrading sulfated polysaccharides: families GH16 (κ-carrageenases, keratanases), GH79 (heparanases), GH82 (ι-carrageenases), a new GH family specific for the degradation of sulfated fucans [46] and two unclassified enzymes, Bacillus circulans keratanase II [47] and P. carrageenovora λ-carrageenase (the present study). With the exception of the GH16 family, all these families encompass enzymes that interact exclusively with anionic polysaccharides.…”
Section: Insights Into the Evolution Of Carrageenase Familiesmentioning
confidence: 81%
“…The CBM16 polypeptides constitute a large family of 59 members that are linked to diverse catalytic domains (17)(18)(19)(20)(21), suggesting that these CBMs possess distinct binding specificities. Until recently, the residues that are key to ligand binding in this family were unknown.…”
mentioning
confidence: 99%
“…This tube was very soft and thin so that we could minimize damage to the spinal cord. The osmotic mini-pumps (200 l of solution, 0.5 l/h, 14 d delivery; Alzet pump model 2002 [Durect]) were filled with K-II (0.05 U/200 l; purified from Bacillus circulans) (Yamagishi et al, 2003), C-ABC (0.05 U/200 l) (Seikagaku), or saline (as a vehicle control). To determine an appropriate dose of C-ABC, we examined several doses and found that at the doses of 0.05, 0.1, and 1.0 U/200 l, C-ABC showed a comparable effect on motor function recovery, while the dose of 0.025 U/200 l showed a less potent effect (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We purified K-II from B. circulans as previously described (Yamagishi et al, 2003). Although the extracts of B. circulans showed both keratanase and chondroitinase activities, our stepwise protocol completely abolished the chondroitinase activity and purified K-II (Table 2).…”
Section: In Vitro and In Vivo Degradation Of Ks By K-iimentioning
confidence: 99%
See 1 more Smart Citation